Divergência entre prática e recomendações para modelos de atuação do PMO: o caso de uma empresa de grande porte do setor industrial - Fernandes, Thiago Henriques (2016)
The objective of this work was to identify what are the main divergences found between what the theory preconizes as scope and approach of the Project Management Offices (PMOs) and what really happens when practice is observed on site. Such intend was achieved with the support of a case study analysis. The theme may be considered relevant based on the fact that it provides a better comprehension about how the PMOs structures really operate. Specially regarding to scope, that is, whether the PMO is a Program-Project, a Departmental PMO, or a Corporate PMO, and regarding its range, that is, if its action is operational, tactical or strategic. Qualitative methodology was used in this research, through a case study approach. A large size manufacturing company not structured by projects was chosen to be evaluated. This company has a complex organizational structure and such characteristic makes possible a comprehensive study. The performance of the PMOs addressed in the case study was discussed taking in consideration the literature and also the information collected from the participant observation. The results of this work allows to conclude that the assumption of the research, that there are divergences between what the theory preconizes as scope and approach of the PMOs and what really happens on practice, is confirmed through the case study. Beyond that, there is not a clear causality relation between the amplitude of action of those PMOs and its hierarchic position within the organization. Also there is not a pattern of action of the PMOs when compared to functions that they perform. Finally, recommendations were made related to the case study presented. The main ones are shown as follows. It is important to hold a multi case study for a better comprehension of the theme with at least one company structured by projects and other one non-structured by projects in order to compare the performance of their PMOs aiming to better understand the theme. To include more stakeholders among the group of the interviewed people within the case study. To hold a survey with various companies of various segments inside the national territory. Also to perform a study where it may be verified whether different organizational typologies may affect the practice of PMOs in the organizations.